Litigating Challenges to Executive Pay: An Exercise in Futility? - Randall S. Thomas; Kenneth J. Martin (Washington University Law Quarterly, 2001)
This Article focuses on the last of shareholders’ alternatives: suing. Shareholder derivative litigation has frequently been an engine for changing abusive corporate practices. The well-tested claims of breach of duty of care, breach of duty of loyalty, and waste, are available when the appropriate facts support them. In recent history, a large number of determined plaintiffs have brought such claims, challenging abusive corporate pay practices in corporations.
Keywords: Executive compensation; Stockholders& #x27; derivative actions; Smith v. Van Gorkom 488 A.2d 858 (Del. 1985); Chief executive officers; Wages and salaries; American Law Institute